„O powszechną płci naszej chwałę”: Tłumaczki epoki stanisławowskiej - Karolina Dębska (Ksiegarnia Akademicka Publishing, 2019)
“For the Universal Glory of Our Sex”: Women Translators in the Times of King Stanisław August